Antiproliferative Fatty Acids Isolated from the Polypore Fungus Onnia tomentosa - Hooi Xian Lee; Wai Ming Li; Jatinder Khatra; Zhicheng Xia; Oleg Sannikov; Yun Ling; Haoxuan Zhu; Chow H. Lee (Journal of Fungi, 2022)
Onnia tomentosa is a widespread root rot pathogen frequently found in coniferous forests in North America. In this study, the potential medicinal properties of this wild polypore mushroom collected from north–central British Columbia, Canada, were investigated. The ethanol extract from O. tomentosa was found to exhibit strong antiproliferative activity. Liquid–liquid extraction and bioactivity-guided fractionation, together with HPLC-MS/MS and 1D/2D NMR analyses of the ethanol extract of O. tomentosa, led to the identification of eight known linoleic oxygenated fatty acids (1.1–1.4 and 2–5), together with linoleic (6) and oleic acids (7). The autoxidation of linoleic acid upon isolation from a natural source and compound 5 as an autoxidation product of linoleic acid are reported here for the first time. GC-FID analysis of O. tomentosa, Fomitopsis officinalis, Echinodontium tinctorium, and Albatrellus flettii revealed linoleic, oleic, palmitic, and stearic acids as the major fatty acids. This study further showed that fatty acids were the major antiproliferative constituents in the ethanol extract from O. tomentosa. Linoleic acid and oleic acid had IC50 values of 50.3 and 90.4 µM against human cervical cancer cells (HeLa), respectively. The results from this study have implications regarding the future exploration of O. tomentosa as a possible edible and/or medicinal mushroom. It is also recommended that necessary caution be taken when isolating unstable fatty acids from natural sources and in interpreting the results.